Analysis of age, refractive error and gender related changes of the cornea and the anterior segment of the eye with Scheimpflug imaging - AKMAN, MEHMET (ELSEVIER, 2015)
Purpose: To assess age, refractive error and gender related changes occurring in the cornea and the anterior segment of the eye using a Scheimpflug system. Methods: The study included 666 healthy eyed subjects with a mean age of 39.3 +/- 19.7 years (range: 3-85 years). All analyses were based on the right eyes of the patients as all measured parameters correlated well between the right and left eyes. Each parameter was correlated with age and the right eye's spherical equivalent (SE) using Pearson correlations. Univariate linear regression models were constructed for analyses of parameters. Results: The anterior corneal surface asphericity showed significant positive correlations whereas posterior corneal surface asphericity showed significant negative correlations with age. Anterior chamber depth (ACD), volume (ACV) and angle (ACA) showed significant negative correlations with age and SE. Age explained 25% of the variance in anterior corneal surface asphericity, 22% of variance in posterior corneal surface asphericity, 26% of variance in ACV, 27% of variance in ACD, and 19% of variance in ACA. In the SE model SE was identified to account for 25% of variance in ACV, 22% of variance in ACD, each, and 17% of variance in ACA. Significant differences were detected in anterior and posterior keratometry values, ACV, ACD and ACA among gender groups (p <0.01). Conclusions: The cornea shows a tendency for a decrease in anterior corneal surface asphericity and an increase in posterior corneal surface asphericity with advancing age. Men have flatter corneas and women have shallower anterior chambers and narrower anterior chamber angles. (C) 2015 British Contact Lens Association. Published by Elsevier Ltd. All rights reserved.
Keywords: Cornea; Anterior chamber; Aging; Gender; Refraction; Pentacam; INTRAOCULAR-PRESSURE; CHAMBER ANGLE; AXIAL LENGTH; ASPHERICITY; ASTIGMATISM; THICKNESS; BIOMETRY; DEPTH; SHAPE; POPULATION